The Effect of Earnings Aggressiveness, Earnings Smoothing on Return of Stock - Khaddaf, Muammar; ., Khaira Amalia F; ., Rahmanta (Journal of Economics and Behavioral Studies, 2014)
This study aims to examine the moderating role of trading volume activity and cost of equity between earnings aggressiveness and earnings smoothing on return of stock. It includes the analysis of earnings persistent in strengthening the relationship between earnings aggressiveness, earnings smoothing, the cost of equity and trading volume activity as well as their effect on return of stock. The sample of study is 32 banking companies which pay dividends and which shares actively traded at the Indonesian Stock Exchange (BEI) whereby the period of observation took place from 2007 to 2011. The method uses a multiple linear regression analysis using SPSS as the data processing tools. The results of this study establish that the earnings aggressiveness and earnings smoothing simultaneously and significantly affect the trading volume activity. The earnings smoothing has a negative effect and is significant on the trading volume activity, while earnings aggressiveness has a positive effect and is significant on the trading volume activity. Meanwhile, the trading volume activity has positive effect and is significant on return of stock and the earnings persistence is moderating the relationship between earnings aggressiveness and earnings smoothing on the trading volume activity.